Aluminium oxide formation via atomic layer deposition using a polymer brush mediated selective infiltration approach - Snelgrove, Matthew; Mani Gonzalez, Pierre Giovanni; McFeely, Caitlin; Lahtonen, K; Lundy, Ross; Hughes, Greg; Valden, M; McGlynn, Enda; Yadav, Pravind; Saari, J; Morris, Mike A; O Connor, Robert (2020)
Area selective deposition (ASD) is an emerging method for the patterning of electronic devices as it can significantly reduce processing steps in the industry. A potential ASD methodology uses infiltration of metal precursors into patterned polymer materials. The work presented within demonstrates this potential by examining hydroxy terminated poly(2-vinylpyridine) (P2VP-OH) as the ‘receiving’ polymer and trimethylaluminium (TMA) and H2O as the material precursors in a conventional atomic layer deposition (ALD) process. Fundamental understanding of the surface process was achieved using X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray spectroscopy (EDX) mapping via transmission electron microscopy (TEM). The resulting analysis confirms aluminium inclusion within the polymer film. Spectroscopic and microscopic characterisation show metal infiltration throughout the polymer to the …